PENGARUH INOVASI PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KITCHEN SET DI PT. NIAGA SARAE INTERMEDIA - Herawati, Sinta; Halim, Prihartono Aksan (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
This research aims to determine how product innovation and pricing influence the purchasing decisions for kitchen sets at PT Niaga Sarae Intermedia. A quantitative method was used with a population of 225 individuals, derived from consumers who purchased kitchen set products, and a sample size of 70 respondents. The Slovin formula was used for sample selection. Data testing included validity and reliability tests, significance tests, multiple linear regression analysis, and the determination coefficient, conducted using SPSS V.7 software. The results of the tests indicate that partially, product innovation and pricing factors influence the purchasing decisions for kitchen sets at PT Niaga Sarae Intermedia. Furthermore, product innovation and pricing have a positive impact on purchasing decisions simultaneously. These findings assist the company in maintaining a competitive advantage in the market and developing effective marketing strategies.